Sodium aluminates obtained from the al(no3)3 • 9h2o — naoh system using the controlled precipitation method (2010)
Sodium aluminate, NaAlO2• xH2O, is an important comer- cial chemical used in water treatment, as a source of alumi- nium in the preparation of zeolites and other catalytic mate- rials and as an additive in paper manufacturing. Sodium alu- minates were synthesised in this work by using the Al(NO3)3 •9H2O- NaOH system’s controlled precipitation method. Using the controlled precipitation method enabled identifying the process’s different stages from potentiometric titration of Al(NO3)3 • 9H2O dissolved in water and using NaOH as precipitating agent to ensure control and reproducibility and also identify final product characteristics. Powders were characterised by infrared spectroscopy (FTIR), X-ray diffraction (XRD) and gravimetric and differential thermal analysis. The results indicated that NaAlO2 crystallised well at 1,000°C (obtained as the main crystalline sodium aluminate phase) and that β-alumina treatment began to form at 1,500°C.